Stabilometric profile of handstand technique in male gymnasts - Sobera, M.; Serafin, R.; Rutkowska-Kucharska, A. (Acta of Bioengineering and Biomechanics, 2019)
Purpose: This study aimed to determine the characteristic features of handstand posture control associated with a high level of ability among male gymnasts. Methods: 8 acrobatic gymnasts (4 more and 4 less experienced) participated in the study. They performed a 10-second handstand five times with each hand positioned on one AccuSway (AMTI) force platform and the other hand on the second. Body sway changes were recorded in time series: centre of pressure (COP) and components of the ground reaction force (GRF) (vertical, medial-lateral and anterior-posterior). The COP amplitude and average of GRF components, the index of frequency (by Fast Fourier Transform) for the right and left hand were calculated. Results: More experienced gymnasts performing a handstand concentrate mainly on minimizing anterior-posterior body sway with minimum medial-lateral body sway. Less experienced gymnasts` pressure exerted on a surface by the hands is irregular in a medial-lateral direction. More experienced gymnasts control body position in the handstand and show less variation of body sway compared to less experienced gymnasts. More experienced gymnasts revealed lower frequency of body sway in the handstand compared to less experienced gymnasts.